Opinions of a group of young adult men towards psychoactive substance use - Ebrinç, Servet; Başoğlu, Cengiz; Çetin, Mesut; Karaduman, Ferit; Çobanoğlu, Necati; Maden, Beyhan (Journal of Dependence, 2002)
Objective: The aim of this study was to determine whether there exists any difference between substance users and nonusers with regards to opinions and moral values about substance abuse. Methods: In the study, 1945 young adult male subjects complete questionnaire inquiring sociodemographic variables and subjects opinions towards cigarette, alcohol and psychoactive substance use. All statistical assessments were conducted by dividing the 1600 subjects who successfully completed the questionnaire into three subgroups, i.e. non-users, substance users and the ones who tried. Results: More than 50% of all three subgroups had the common idea that “they had lack of knowledge concerning substances and its abuses”. The items about marihuana “is not more dangerous than cigarette and alcohol”; “not causing dependency”; “do not result in co-dependency”; and “psychoactive substance helps individual gets away form his daily problems” were more commonly agreed by substance users than non-users, whereas they less frequently agree to the item stating ”willpower insufficiency increases substance use”. Other items that substance users more commonly agree were; “Having problems increases substance use”; “individual could control substance use”; “one time substance use do not carry any risk” and “because of strong willpower they have, they would notr be dependent even if they try the substance”. Conclusion: As a conclusion, it was determined that individuals who try or use substances have a risky selftrust towards substance use and have cognitive difficulties in perception of the importance of psychoactive substance use